Old age in Northern Ireland - study of elderly in a sea-side town - Harrison, E;; McKeown, M; O' Shea, T (Economic & Social Studies, 1971)
Northern Ireland's social policy is governed by the principle of parity with Britain. This means that British measures of social welfare are usually adopted in Northern Ireland. There are often administrative modifications, but, there is usually no systematic attempt to idiscover whether the measures suit the social characteristics of the Northern lrish people. Services for the aged exemplify this situation.
Keywords: Ageing; Northern Ireland